Creativity Skill Proses in Project Based Learning: A Case Study of Distance Learning in Pacitan - V. Ardhyantama; S. Widodo (Randwick International of Education and Linguistics Science Journal, 2020)
Learning creativity skill is important for students. Distance learning during the Covid-19 period is the best option for study. However, students' needs among cognitive, affective, psychomotor and various skills need to be well accommodated. This study aims to describe the process of creativity in project-based learning in distance learning. The research subjects were 10 elementary school education students grade 2nd. The learning project was carried out at home with online guidance and discussion due to the conditions of Covid-19 which made it impossible to gather. The learning project that is designed is to create a learning media for beginning reading for elementary school students. Wallas' creative process includes 5 stages: preparation, incubation, intimacy, illumination and verification. Distance learning projects are carried out in 7 stages, namely: (1) formulating learning outcomes, (2) understanding concepts, (3) skills training, (4) designing the project, (5) making the project proposal, (6) executing projects and (7) project report. The results showed that in distance project learning can still be done to train creativity with paying more in accessibility of communication and following the learning stage